2017
DOI: 10.1093/toxsci/kfx124
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Arsenic Induces Hippocampal Neuronal Apoptosis and Cognitive Impairments via an Up-Regulated BMP2/Smad-Dependent Reduced BDNF/TrkB Signaling in Rats

Abstract: Arsenic promotes hippocampal neuronal damage inducing cognitive impairments. However, mechanism arbitrating arsenic-mediated cognitive deficits remains less-known. Here, we identified that chronic exposure to environmentally relevant doses of arsenic increased apoptosis, characterized by caspase-3 activation, poly(ADP-ribose) polymerase cleavage and Terminal deoxynucleotidyl transferase dUTP nick-end labeling of rat hippocampal neurons, marked by NeuN. Investigating apoptotic mechanism through invivo and invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…Another study proved that As can reduce mitochondira membrane potential (MMP) and decrease BDNF gene expression in As treated human neuroblastoma SH-SY 5 Y cells [42]. As induces hippocampal neuronal apoptosis through an up regulated none morphogenic protein 2 (BMP2), Smad dependent attenuation of BDNF TrkB pathway resulting cognitive impairments [43]. Moreover, it was also found that subchronic As exposure in chemically depression induced mouse model enhances the depression-like behaviors through the cerebral prefrontal cortex BDNF-TrkB signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…Another study proved that As can reduce mitochondira membrane potential (MMP) and decrease BDNF gene expression in As treated human neuroblastoma SH-SY 5 Y cells [42]. As induces hippocampal neuronal apoptosis through an up regulated none morphogenic protein 2 (BMP2), Smad dependent attenuation of BDNF TrkB pathway resulting cognitive impairments [43]. Moreover, it was also found that subchronic As exposure in chemically depression induced mouse model enhances the depression-like behaviors through the cerebral prefrontal cortex BDNF-TrkB signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…Cryosections of the cerebral cortex from HFD‐fed mice were incubated with fluorescein‐labeled dUTP and TdT (9 : 1) (overnight) and GFAP or β‐tubulin III antibodies and co‐stained with nuclear Hoechst, following the process described earlier (Pandey et al . ). The sections were then photomicrographed under fluorescent microscope and apoptotic index expressed as the number of TUNEL‐positive cells/100 nuclei in GFAP‐expressing astrocytes or β‐tubulin III‐expressing neurons.…”
Section: Methodsmentioning
confidence: 97%
“…Fas/FasL pathway further exacerbated the condition of colitis mice. Studies have shown that the TrkB-PLC/IP3 pathway can inhibit anxiety-and depression-like behaviors, mainly by inhibiting the apoptosis of hippocampal neurons [33][34][35]. In this study, we did not explore the specific mechanism of TrkB-PLC/IP3 pathway on inflammation and apoptosis, and its application in clinical treatment remained to be further studied.…”
Section: Discussionmentioning
confidence: 91%